Phenomenological Study: Analyzing the Role and Meaning of Sports Performance in The Lives of Wheelchair Student-Athletes - Yulianto, Wahyu Dwi; Sukamti, Endang Rini; Fauzi, Fauzi; Prabowo, Trisnar Adi; Astuti, Ristanti Puji; Rakhmawati, Septiana Dwi; Pamungkas, Maulana Aditya; Gontara, Satria Yudi (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to analyze and understand the role and significance of sports performance in the lives of wheelchair student-athletes. It examines how sports help them navigate physical and psychological challenges, contribute to identity formation, and aid in their search for meaning in life. Materials and methods. The study employed a descriptive quantitative approach using a survey analysis method. Additionally, unstructured interviews were conducted to strengthen the research findings and support the discussion. The sample consisted of 48 wheelchair student-athletes, categorized as follows: 12 tennis players, 12 archers, 12 athletes, and 12 fencers. The sample characteristics included an average age of 17.7±8.1 years, training experience of 4.3±4.2 years, and an athletic career duration of 2.1±2.2 years. Among them, 13 athletes have competed at the national level, and 35 at the regional level. The research instrument was a questionnaire comprising 15 statements rated on a 1–4 scale, which has been tested for validity, resulting in four key indicators: (1) Improved Quality of Life, (2) Social Integration, (3) Search for Existence, and (4) Barriers to Participation. Data analysis used descriptive statistics and the Kruskal-Wallis test (p<0.05) to examine group differences. Results. For the Improved Quality of Life indicator, the lowest average score was observed in athletics (13.83), while the highest — in tennis (14.17). Regarding Social Integration, the lowest average score was in athletics (13.50), and the highest — in archery (13.83). For the Search for Existence indicator, the lowest average scores were observed in athletics and fencing (13.58), while the highest score was noted in archery (13.83). Regarding Barriers to Participation, the lowest average score was recorded in fencing (6.75), and the highest — in tennis (7.50). The Kruskal-Wallis value was 0.425 or p>0.05, indicating no significant differences between the four wheelchair sports groups. Conclusions. The findings indicate that wheelchair sports substantially enhance student-athletes’ quality of life across various disciplines. Tennis and fencing recorded the highest perceived quality of life and the lowest barriers to participation. This study underscores the necessity for standardized facilities, enhanced support systems, and greater governmental involvement to improve student-athletes’ experiences. These insights contribute significantly to both wheelchair sports literature and policy development.